Missed a beat: Is it your Ayurvedic drug? - Kavita S Joshi; Gajanan A Panandikar; Yogesh G Kuntalwad; Smrati Bajpai (International Journal of Medical Research and Review, 2016)
24 year male presented with watery diarrhoea, 10-15 episodes/day since 2 days, vomiting, abdominal pain and giddiness since 1 day. Patient was hypotensive and had bradycardia. Rest of systemic examination was normal. ECG showed junctional bradycardia. Serum electrolytes, creatinine, Thyroid Function Tests were within normal limits. Troponin T levels were normal. On enquiry, patient gave history of ingestion of ayurvedic drug Tribhuvankirtiras and mahashankvati for 1 day prior to symptoms, for dyspepsia. Patient was started on inotropic support with fluid correction for hypotension. Clinical diagnosis of arsenic and aconite toxicity was made. The drug samples showed high levels of Arsenic and Mercury. Aconite level could not be done due to unavailability of resources. Diagnosis of drug induced aconite and arsenic toxicity was made. With discontinuation of ayurvedic drugs and supportive management, patient improved symptomatically within 3 days with restoration of normal sinus rhythm.